FORMATION OF CREATIVE THINKING ABILITY OF ELEMENTARY SCHOOL STUDENTS IN NATIVE LANGUAGE CLASSES - Ismoilova Nilufar Odilbek qizi (Bright Mind Publishing, 2025)
This article examines the unique and essential function of native language instruction as the primary pedagogical vehicle for the formation of creative thinking abilities in elementary school students. It argues that language, as the fundamental medium of cognitive construction, provides the ideal platform for cultivating divergent, flexible, and original thought. This discussion synthesizes Vygotskian frameworks of thought-language interdependence with practical, inquiry-based pedagogical strategies. It posits that by prioritizing literary exploration, semantic flexibility, and process-oriented creative composition over rote grammatical drills, educators can effectively develop the foundational creative competencies essential for 21st-century problem-solving and lifelong learning.
Keywords: Creative thinking, elementary education, native language instruction, pedagogical strategies, divergent thinking, cognitive flexibility, literacy, Vygotsky, 21st-century skills, children’s literature, creative writing.